What is a representative voiding pattern in children with lower urinary tract symptoms? Lack of consistent findings in ambulatory and conventional urodynamic tests. Issue 3 (June 2016) - Lu, Y.T.; Jakobsen, L.K.; Djurhuus, J.C.; Bjerrum, S.N.; Wen, J.G.; Olsen, L.H.
Summary: Background: Conventional urodynamics (CU) is a highly standardized evaluation of lower urinary tract function. However, in pediatric patients there is concern that the reliability of measurements could be influenced by development effects and measurement variability, as well as by the unfamiliar clinical environment. Ambulatory urodynamics (AU) provides an alternative to this – it uses natural filling, is measured over a prolonged period, and is conducted in a child-friendly environment. Objective: The aim of this study was to conduct a comparative analysis of AU and CU to evaluate the consistency in voiding patterns obtained with these two methods of urodynamic testing. Study design: Urodynamic parameters obtained by AU and CU methods in 50 pediatric patients aged >5 years were retrospectively analyzed. Voiding patterns were categorized into six types: coordinated contraction, detrusor after-contraction, fluctuated contraction, pre-void contraction, relief voiding, and weak or absent contraction. Voiding patterns were used to determine the repeatability within urodynamic tests and to identify consistency between AU and CU tests. Five urodynamic parameters were quantified and compared between AU and CU: voided volume, flow rate, maximum detrusor pressure, and detrusor pressure at peak flow rate. For inter-observer variation analysis, 100 voiding curves were randomly selected and categorized by two independent observers; inter-observer agreement was evaluated using the kappa statistic. Results: A single pattern of voiding was identified in five patients using AU and 37 using CU. Consistency of a single pattern between AU and CU was identified in three patients, and consistency between a predominant pattern with AU, defined by one type of voiding occurring >50% of one's voids, and a single pattern with CU was identified in 10 patients (summary table). Flow rates were similar between methods; however, higher maximum detrusor pressure and detrusor pressure at peak flow and lower voided volume were recorded with AU. Discussion: AU resulted in more diverse voiding patterns. Along with the differences in measured urodynamic parameters challenges the application of findings from one method to form a clinical diagnosis. Furthermore, CU may not be as sensitive as AU to the variability in lower urinary tract pathophysiology. Conclusions: More diverse voiding patterns were identified in AU compared with CU, with a lack of consistency in identified voiding pattern in both methods. Therefore, the urodynamic findings in children may have to be analyzed in more detail, taking the variations into account. Summary table Voiding patterns identified by ambulatory and conventional urodynamic methods, and consistency between the two methods. Number of voids Repeatability of voiding pattern (number of patients) Consistency between AU and CU (number of patients) CU AU SP in CU SP in AU PP in AU SP in CU–SP in AU SP in CU–PP in AU Type 1 1 21 0 0 1 0 0 Type 2 18 73 8 2 6 1 1 Type 3 55 170 19 2 16 1 7 Type 4 0 4 0 0 0 0 0 Type 5 25 54 8 1 2 1 2 Type 6 4 23 2 0 1 0 0 N 103 345 37 5 26 3 10 AU, ambulatory urodynamics; CU, conventional urodynamics; PP, predominant pattern; SP, single pattern; Type 1, coordinated voiding; Type 2, voiding with detrusor after-contraction; Type 3, voiding with fluctuating detrusor pressure and urine flow; Type 4, pre-void contraction; Type 5, terminal detrusor over-activity leading to relief voiding; Type 6, absence of detrusor contraction during voiding.